2004
DOI: 10.1016/j.cplett.2004.06.056
|View full text |Cite
|
Sign up to set email alerts
|

The role of the catalytic particle temperature gradient for SWNT growth from small particles

Abstract: Abstract:The Vapour-Liquid-Solid (VLS) model, which often includes a temperature gradient (TG) across the catalytic metal particle, is often used to describe the nucleation and growth of carbon nanostructures. Although the TG may be important for the growth of carbon species from large metal particles, molecular dynamics simulations show that it is not required for single-walled carbon nanotube growth from small catalytic particles.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 14 publications
3
62
0
Order By: Relevance
“…Moreover, in agreement with the experiment, it was also found that clusters with diameters smaller than 0.5 nm yield tubes with slightly larger diameters of 0.6 -0.7 nm [151]. Also the effect of temperature gradient was investigated by this group [152,153], concluding that while a temperature gradient may be important for larger particles, it is not required for SWNT growth from small particles.…”
Section: (B) Cnts and Related Structuressupporting
confidence: 64%
“…Moreover, in agreement with the experiment, it was also found that clusters with diameters smaller than 0.5 nm yield tubes with slightly larger diameters of 0.6 -0.7 nm [151]. Also the effect of temperature gradient was investigated by this group [152,153], concluding that while a temperature gradient may be important for larger particles, it is not required for SWNT growth from small particles.…”
Section: (B) Cnts and Related Structuressupporting
confidence: 64%
“…The formation of CNCs and CNTs was not confirmed when the heating temperature was changed to 873 K, 973 K, 1073 K, and 1123 K. When the heating time was shortened to 0.5 h at 1173 K, the size distribution of CNCs and CNTs was similar. size melt at 1000 K [27]. The melting Fe particles are mobile and fuse together.…”
Section: Resultsmentioning
confidence: 99%
“…Jiao et al showed from in situ TEM that in, CNCs encapsulating Fe and Fe carbide particles, the particle is removed from the CNC at 1173-1373 K [29]. As Ding et al discussed, the driving force of the particle removal relates to the temperature and concentration gradients in the particle, which are caused by the precipitation of graphene layers [27]. By removal of the particle, the CNC is broken and a hole is formed.…”
Section: Formation Of Cncs and Cntsmentioning
confidence: 99%
“…all C atoms are dissolved in the particle; (ii) at intermediate times the FeC cluster is highly supersaturated in C and carbon strings, polygons and small graphitic islands nucleate on the cluster surface; (iii) at later times the FeC cluster is supersaturated in C and, depending on the temperature, the graphene sheet, SWCNT, or the soot-like structure grows, as shown in Figures 7C and 8 A. Ding et al [25] also studied the role of the catalyst-particle temperature gradient in SWCNT growth from small particles. The investigation revealed that although the temperature gradient may be important for the growth of carbon species from large metal particles, according to MD simulations, this is not required for the growth of SWCNTs from small catalytic particles.…”
Section: Discrete Computational Modelingmentioning
confidence: 96%
“…In addition, the PES could distinguish between dissolved and precipitated carbon atoms. With the help of PES, the authors could also describe the role of the catalytic particle temperature gradient [25,26] and the influence of catalyst particle size in nanotube growth [27] , and in a bamboo-like CNT formation [28] . The approach and results were novel in this aspect.…”
Section: Discrete Modelsmentioning
confidence: 99%